Computational Study of Critical Flow Discharge in Supercritical Water Cooled Reactors - Chatharaju, Madhuri (My University, 2011)
Supercritical Water-cooled Reactor (SCWR) is a Generation-IV nuclear reactor design that operates on a direct energy conversion cycle above the thermodynamic critical point of water (3740C and 22.1 MPa), and offers higher thermal efficiency and considerable design simplification. As an essential step in the design of SCWR safety systems, the accident behaviour of the reactor is evaluated to ensure that the safety systems can achieve safe shutdown for all the design basis accidents. Unfortunately, the computational tools and computer codes that are currently employed for safety analysis have little application in the supercritical region, and faces significant challenges in simulating the transitions from subcritical to supercritical conditions.
This thesis examines the predictive capabilities of Computational Fluid Dynamics (CFD) code STAR-CCM+ by evaluating critical flow (or choked flow) due to accidental release of coolant from supercritical fluid systems. The biggest challenge of this research is that the current version of STAR-CCM+ does not support supercritical simulations because the steam tables included in the package are only limited to the subcritical subset of the thermodynamic fluid properties.
The research was carried out in two stages. In the first stage, the CFD code STAR-CCM+ was customized to simulate supercritical conditions by, (i) Generating updated steam tables to include subcritical and supercritical fluid properties and using more pressure and temperature points in the pseudo critical region (22 – 25 MPa, 645 -660 K) to handle the rapid changes in the fluid properties, and (ii) Implementing a multi-dimensional steam table interpolation scheme to access the fluid property data at any thermodynamic state during the simulation. In the second stage, the customized CFD code was extensively evaluated by simulating several accidental release scenarios from supercritical conditions using rounded-edge and sharp-edge nozzles and the model results were validated with experimental data. To overcome the solution stability (or convergence) issues encountered during the supercritical simulations, a fine tuning procedure was proposed that guaranteed convergence for all the case studies considered in this thesis.
The simulation results revealed that the CFD model produced results that were in good agreement with experimental data and only about 10% prediction error was noticed for most cases considered in the thesis. Considering the sensitivity of the CFD model for upstream temperatures and pressures, these results appear to be quite reasonable. From the computational experience gained in this research , we believe that the CFD code STAR-CCM+ is a very useful tool to perform thermal hydraulic simulations for supercritical systems. However, an appropriate customization and extensive validation of the code is required before it can be exclusively used for safety analysis.
Keywords: Supercritical water cooled reactors; LOCA; Critical flow; Thermal hydraulics; Safety Analysis; CFD; STAR-CCM+; Nuclear Engineering; Nuclear Engineering